Twenty-six seconds : a personal history of the Zapruder film - Zapruder, Alexandra (Twelve, 2016)
The family story behind Abraham Zapruder's film footage of the Kennedy assassination and its lasting impact, told by Zapruder's granddaughter, draws on personal records and previously sealed archive sources to trace the film's role in the media, courts, government, and arts community.--